Health system strengthening using a Maximizing Engagement for Readiness and Impact (MERI) Approach: A community case study - Kyomuhangi, Teddy; Manalili, Kimberly; Kabakyenga, Jerome; Turyakira, Eleanor; Matovelo, Dismas; Khan, Sobia; Kyokushaba, Clare; MacIntosh, Heather; Brenner, Jennifer L. (Frontiers in Public Health, 2022)
Introduction Health system strengthening initiatives in low and middle-income countries are commonly hampered by limited implementation readiness. The Maximizing Engagement for Readiness and Impact (MERI) Approach uses a system ‘readiness’ theory of change to address implementation obstacles. MERI is documented based on field experiences, incorporating best practices, and lessons learned from two decades of maternal, newborn, and child health (MNCH) programming in East Africa. Context The MERI Approach is informed by four sequential and progressively larger MNCH interventions in Uganda and Tanzania. Intervention evaluations incorporating qualitative and quantitative data sources assessed health and process outcomes. Using an implementation lens and an implementation science readiness theory of change, reflection on sequential experiences enabled model MERI Approach adaptation and documentation. Key Programmatic Elements The MERI Approach comprises three core components. MERI Change Strategies (meetings, equipping, training, mentoring) describe key activity types that build general and intervention-specific capacity to maximize and sustain intervention effectiveness. The SOPETAR Process Model (Scan, Orient, Plan, Equip, Train, Act, Reflect) is a series of purposeful steps that, in sequence, drive each implementation level (district, health facility, community). A MERI Motivational Framework identifies foundational factors (self-reliance, collective-action, embeddedness, comprehensiveness, transparency) that motivate participants and enhance intervention adoption. Components aim to enhance implementer and system readiness while engaging broad stakeholders in capacity building activities towards health outcome goals. Activities align with government policy and programming and are embedded within existing district, health facility, and community structures. Discussion Use of the MERI Approach to support district wide MNCH programming in two low-income countries was feasible and supportive of health outcome and health system improvements. The MERI Approach has potential to engage districts, health facilities, and communities towards sustainable health outcomes, addressing intervention implementation gaps for current and emerging health needs within and beyond East Africa.